Double-layered reactive microcapsules with excellent thermal and non-polar solvent resistance for self-healing coatings. Issue 8 (22nd January 2015) - Sun, Dawei; An, Jinliang; Wu, Gang; Yang, Jinglei
Abstract : Diisocyanate was encapsulated with a double-layered wall possessing superior resistance to non-polar organic solvents. Abstract : Double-layered polyurea microcapsules containing hexamethylene diisocyanate (HDI) with outstanding shell tightness have been successfully synthesized via interfacial polymerization reaction in an oil-in-water emulsion. The resultant capsules were systematically characterized by scanning electron microscopy (SEM), thermogravimetric analysis (TGA) and Fourier transform infrared (FTIR) spectroscopy. The reaction parameters including reaction temperature (40 °C, 50 °C, 60 °C), reaction duration (1 h, 1.5 h, 2 h and 2.5 h), amount of Suprasec 2644 (2.4 g, 3 g and 3.6 g) and emulsification time (15 min, 45 min and 75 min) were investigated and evaluated in terms of core fraction and quality of microcapsules. The core fraction of microcapsules was reduced with an increase of reaction temperature, reaction duration, mass of Suprasec 2644 and emulsification time, while the quality of microcapsules fluctuated. The thermal and organic solvent resistances were assessed by using TGA and titration. The results showed that the microcapsules had 1.6% weight loss compared with pure HDI with 90% weight loss after 60 min isothermal treatment at 100 °C. After immersion in various solvents for 24 days, the microcapsules released as low as ∼3% of core in weakly polar solvents ( i.e. hexane and xylene), about 5–60% in polar aprotic solvents ( i.e. ethyl acetate, acetone, DMF and DMSO), and 60–90% in water and polar protic solvents ( i.e. isopropanol and ethylene glycol). Both fresh and hexane-treated HDI capsules showed excellent anticorrosion performance in scratched coatings via self-healing functionality, indicating promising practical application in industrial coating and paint systems.